Evaluation of Uniformity Coefficient and Water Distribution Efficiency of Some Impact Sprinklers in Shambat, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was carried out during May and June 2010 in theDemonstration Farm of the Faculty of Agriculture, University ofKhartoum at Shambat, to evaluate water distribution under different typesof sprinkler heads. The study consisted of evaluating Christiansen'scoefficient of uniformity (CU %) and uniformity of distribution (DU %)under twin nozzle brass impact sprinkler (JIS2), twin nozzle plasticsprinkler (DAN4455) and single nozzle plastic sprinkler (LEGO55). Thetwin nozzle brass sprinkler gave significantly better values for allsprinkler configurations, while the difference between twin and singlenozzle plastic sprinklers was mostly insignificant. At low wind speeds(